BLADE RUNNER: FANTASY OR FORECAST? Drivers and Upshots of Robots Becoming Identical, Enhanced Replications of Us - Kuhns, William (New Explorations, 2024)
Of the two spiraling threads that make up the DNA of AI, this paper argues, one is algorithmic, the other is anthropic. This paper argues that, due to seven powerful drivers, 150% Synthetic Humans, that is, fully engineered “artificial persons” with brains, senses, bodies and durability augmented beyond our own, may be irrevocably baked into evolving Artificial Intelligence. If this is the case, what risks would humans face and how would those risks balance with the advantages we’d reap? In the 1982 classic Blade Runner, the Tyrell Corporation boasts that physically and mentally upgraded versions of you and me are “more human than human.” This paper presents seven reasons – both conscious and subliminal -- why the evolution of AI appears to be on track toward the manufacturing of high-definition, “better developed” human doppelgangers. The drivers: 1) Form follows function; 2) We are the anthropomorphizing species; 3) Synthetic companionship; 4) Current computer chat is only 7% of the way there; 5) The Turing Test; 6) The Bioengineering factor; 7) The Subliminal Grand Commandment enforced by media culture: in mechanically enabled replications, we seek exalted versions of ourselves. Four prospective downsides of building all-too-human humanoids are discussed, as are preventive and resistance measures. The issue of robot doppelgangers may prove more problematic for humans than AI superintelligence. Indeed, the day may come when the acronym “AI” comes to signify “Abundantly Identical.”